SISTEM PEMBARUAN OTOMATIS PERANGKAT LUNAK PADA SISTEM KENDALI PESAWAT TERBANG, STUDI KASUS: MCAS BOEING 737 MAX - Muhammad Alfandy Pramana Lubis Fandy; Reo Yudhono; Muhammad Luqman Bukhori (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
Maneuvering characteristic augumentation system is a computer system used to prevent excessive nose up on Boeing 737 Max aircraft, the higher the nose up of the aircraft will cause the aircraft to lose lift force (stall). The system was created to compensate for the new engine shifts on boeing 737 Max aircraft that are likely to be in the future, but this is not offset by the new center of gravity calculations. So that the aircraft has a tendency to always nose up, so that with the MCAS system, it can avoid aircraft tending to nose up. However, due to the MCAS system's misreading of the actual position of the aircraft, MCAS will control the elevator so that the aircraft can nose down, because the pilot has not been able to turn off MCAS, the pilot has difficulty controlling the aircraft and the aircraft has an accident. Based on these problems, researchers made a software design to replace MCAS that has the ability to update and calibrate automatically to detect the angle of attack state of the aeromodelling aircraft. The software used in this study is integrated with LED indicators and buzzers, then connected with servo elevators. LEDs and buzzers are used to notify in the event of a failure of the angle of attack reading between the software and the actual position of the aircraft. The results showed that the software design can work well by integrating XAMPP, data server websites, MySQL, and Apache. When there is a failure to read the angle of attack, the LED and buzzer will light up, then connect the display server to XAMPP, Apache and MySQL. Once all are connected then calibration will be carried out and data will be sent to the aircraft system.